AB0899 TREATMENT STATUS OF PATIENTS WITH GLUCOCORTICOID-INDUCED OSTEOPOROSIS IN THE AKITA ORTHOPEDIC GROUP ON RHEUMATOID ARTHRITIS REGISTRY. (2nd June 2020) - Kawano, T.; Kashiwagura, T.; Kobayashi, M.; Sugimura, Y.; Sato, H.; Miyakoshi, N.; Shimada, Y.
Abstract : Background: Glucocorticoids (GC) have potent anti-inflammatory and immunosuppressive effects and are used to treat a variety of diseases. However, GC are associated with several adverse effects. Glucocorticoid-induced osteoporosis (GIO), a bone metabolism disorder, accounts for 25% of the side effects associated with GC, and long-term use of these agents leads to fragility fractures in 30 to 50% of patients [1]. GC are frequently used to treat rheumatoid arthritis (RA). No report on the current treatment status for glucocorticoid-induced osteoporosis (GIO) has been published following the publication of the new guidelines for the management and treatment of GIO issued by the Japanese Society for Bone Mineral Research provided in 2014 (Figure 1 ) [2]. Objectives: The present study aimed to investigate the current treatment status of GIO patients in the Akita Orthopedic Group on Rheumatoid Arthritis (AORA) registry. Methods: This retrospective, multicenter study included 683 patients (138 men, 545 women) with fracture risk factor scores ≥3 based on the new guidelines who were in the AORA registry. We examined patient characteristics, differences in patient backgrounds between treated and non-treated groups. Results: There were no significant differences in mean GC dose between men and women (4.0 ± 2.3 mg/day vs 3.6 ± 1.8 mg/day, p = 0.08). The mean disease duration of RA in women was significantly longer than in men (180.2 ± 140.2 months vs 143.8 ± 129.6 months, Untreated GIO patients were significantly more likely to be men and younger. The univariate analysis showed that clinic visits, male sex, younger age, and longer disease duration were significant risk factors for lack of therapeutic intervention for GIO. Multivariate analysis showed that being treated in a clinic, male sex, and younger age were significant risk factors for lack of therapeutic intervention for GIO. Conclusion: Our results emphasize the importance of considering the prevention and treatment of GIO in all patients with RA, including younger and male patients, who have lower intervention rates. References: [1]Weinstein RS. Clinical practice. Glucocorticoid-induced bone disease. New Engl J Med. 2011; 365(1): 62-70. [2]Suzuki Y, Nawata H, Soen S, Fujiwara S, Nakayama H, Tanaka I, et al. Guidelines on the management and treatment of glucocorticoid-induced osteoporosis of the Japanese Society for Bone and Mineral Research: 2014 update. J Bone Miner Metab. 2014; 32(4): 337-350. Disclosure of Interests: None declared